Optimizing the Personalized, Risk-Adjusted Management of Pulmonary Embolism: An Integrated Clinical Trial Programme - Barco, Stefano; Konstantinides, Stavros V. (Hämostaseologie, 2019)
Acute pulmonary embolism (PE) contributes significantly to the global burden of cardiovascular disease. The severity of the acute PE event determines the expected estimated risk of early death. This risk is influenced by the degree of dysfunction of the right ventricle (RV), as assessed by the presence of acute RV pressure overload on imaging and/or elevated cardiac biomarkers, and by demographic and clinical factors, including relevant comorbidities. Haemodynamic instability and cardiogenic shock is at the top of the PE severity spectrum, as it represents the most extreme manifestation of RV failure and a key determinant of poor prognosis. Ideally, risk-adjusted treatment should implement: (1) optimized timing and regimens of reperfusion therapy for unstable patients; (2) early discharge and continuation of anticoagulation treatment at home (low-risk PE); or (3) hospital admission and clinical/haemodynamic monitoring in patients at intermediate risk. The challenge is now to provide the basis for a comprehensive personalized, risk-adjusted care for patients with acute PE. The aim of the integrated academic clinical trial programme of the Center for Thrombosis and Hemostasis at the University of Mainz is to develop and prospectively validate, in multinational studies, strategies for reperfusion and anticoagulant treatment of acute PE across the entire spectrum of early risk as well as clinical pathways for post-PE patient care and follow-up.
Keywords: pulmonary embolism; risk stratification; clinical trials; anticoagulation; systemic thrombolysis